Prosthetic infection: improvement of diagnostic procedures using 16S ribosomal deoxyribonucleic acid polymerase chain reaction - Höppchen, Arnold; Kommerell, Mechthild; Geiss, Heinrich K.; Burckhardt, Irene; Zimmermann, Stefan; Zeifang, Felix; Lehner, Burkhard (International orthopaedics, 2013)
Prosthetic infection is the worst complication in joint arthroplasty. The diagnostic procedure is time consuming and in many cases unrewarding. The aim of this investigation was to raise the sensitivity of the diagnostic procedure.
Published online: 6 August 2013
Gesehen am 22.03.2022